Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Pandora Press, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. –back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Section: 99 p.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis